Making Race : Modernism and "Racial Art" in America - Francis, Jacqueline (Book collections on Project MUSE., 2012)
"A comparative history of New York expressionist painters Malvin Gray Johnson (1896-1934), Yasuo Kuniyoshi (1893-1953), and Max Weber (1881-1961)"--